2020
DOI: 10.1039/c9ra08504a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the coordination of π-acceptor 4-cyanopyridine ligand on the structural and electronic properties ofmeso-tetra(para-methoxy) andmeso-tetra(para-chlorophenyl) porphyrin cobalt(ii) coordination compounds. Application in the catalytic degradation of methylene blue dye

Abstract: Preparation and UV/vis, IR, MS, 1H NMR, cyclic voltammetry and molecular structures of two new Co(ii) complexes with para-methoxy-phenyl and para-chloro meso-porphyrins and 4-cyanopyridine ligand (1–2). Catalytic oxidation data of MB dye using 1–2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 69 publications
2
26
0
1
Order By: Relevance
“…In the Kubalka‐Munk converted diffused reflectance spectrum (DRS) of CoTMPP molecule, the characteristic soret band (B) is observed at 428 nm, along with a shoulder at ∼390 nm (Figure 2a). The Q bands appeared in the range of 500–680 nm (A), and the one with the highest intensity was at around 530 nm, which is in good agreement with the previous repors available in the literature [50] . The solid‐state diffused reflectance spectrum of CTMZ‐8 has characteristic features of the DRS of CoTMPP but interestingly, the entire electronic absorption has experienced a blue shift as can be seen from Figure 2a.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In the Kubalka‐Munk converted diffused reflectance spectrum (DRS) of CoTMPP molecule, the characteristic soret band (B) is observed at 428 nm, along with a shoulder at ∼390 nm (Figure 2a). The Q bands appeared in the range of 500–680 nm (A), and the one with the highest intensity was at around 530 nm, which is in good agreement with the previous repors available in the literature [50] . The solid‐state diffused reflectance spectrum of CTMZ‐8 has characteristic features of the DRS of CoTMPP but interestingly, the entire electronic absorption has experienced a blue shift as can be seen from Figure 2a.…”
Section: Resultssupporting
confidence: 89%
“…The enhancement of electrochemical OER activity of the CTMZ‐8 composite than either of its constituents i. e ., ZIF‐8 and CoTMPP, is a direct consequence of the synergistic interaction between the guest CoTMPP and the host ZIF‐8 ( vide supra ). Earlier Freire and co‐workers also showed that, synergistic interaction between guest material and ZIFs could positively affect the observed OER of the composite formed [50] …”
Section: Resultsmentioning
confidence: 86%
“…60 According to the literature, the degradation yield of BM dye obtained using our Co(II)-porphyrin compound (84%) is comparable and in some cases even superior to those of previously synthesized and studied cobalt metalloporphyrins. 17 On the other hand, this degradation yield is lower than those obtained with metalloporphyrin polymers (99%). 61 For CV dye degradation, the yield obtained (90%) is quite acceptable for the rst reported investigation of the degradation of this dye using a porphyrin derivative.…”
Section: The Catalytic Degradation Of Methylene Blue and Crystal Violetmentioning
confidence: 83%
“…The E 1/2 values of H 2 TMAPP are close to those of meso-porphyrin (Table S2 †). 17,39 Concerning our Co(II)-TMAPP derivative (2), it presents three one-electron reversible oxidations (Fig. 3b), where the rst corresponds to the center metal [Co(II)/Co(III)] (MO2) oxidation followed by two ring oxidations, with an E ap (E ap ¼ anodic peak potential) value of 0.61 V; this is in the range of 0.60-0.98 V, which has been shown in several solvents for cobalt metalloporphyrins (Table S2 † O4)).…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation